A high-solid DES pretreatment using never-dried biomass as the starting material: towards high-quality lignin fractionation. Issue 4 (1st February 2023) - Cheng, Jinyuan; Huang, Chen; Zhan, Yunni; Liu, Xuze; Wang, Jia; Meng, Xianzhi; Yoo, Chang Geun; Fang, Guigan; Ragauskas, Arthur J.
Abstract : This study investigated a high-solid diol deep eutectic solvent (DES) pretreatment using a wet substrate as the starting material. Abstract : This study investigated a high-solid diol deep eutectic solvent (DES) pretreatment using a wet substrate as the starting material. This pretreatment led to a remarkable glucan saccharification of 94.8% with efficient lignin and xylan removal (as high as 63.1% and 73.0%, respectively). The chemical structures of the substrates were analyzed comprehensively to reveal the impact of the pretreatment. In addition, over 90% of the removed lignin was recovered from the pretreated liquid, which exhibited a well-preserved β-O-4 structure (46–56/100Ar). The protection mechanism of our DES was investigated by 2D HSQC NMR, GPC, and 31 P NMR analysis. This study emphasized that diol-based DES pretreatment of undried lignocellulosic biomass at a high-solid loading can significantly utilize both carbohydrates and lignin fractions with high saccharification yields and high-quality lignin as a co-product.